AtSTP11, a pollen tube-specific monosaccharide transporter in Arabidopsis. - Schneidereit, Alexander; Scholz-Starke, Joachim; Sauer, Norbert; Büttner, Michael (Planta, 2005)
Pollen development, as well as pollen germination and pollen tube growth, requires a highly regulated supply of sugars. In this paper we describe the molecular, kinetic, and physiological characterization of AtSTP11, a new member of the H+/monosaccharide transporter family in Arabidopsis thaliana (L.) Heynh. Heterologous expression in yeast (Saccharomyces cerevisiae) showed that AtSTP11 is a high-affinity (Km = 25 microM), broad-spectrum, and uncoupler-sensitive monosaccharide transporter of the plasma membrane. In reverse transcription-polymerase chain reaction analyses we found that AtSTP11 expression is restricted to flowers. Furthermore, AtSTP11-promoter::GFP plants revealed that AtSTP11 expression is only found in pollen tubes. Using a specific antibody we could also detect the AtSTP11 protein exclusively in pollen tubes but not in other flower tissues or in pollen grains of any developmental stage. These results suggest that the newly identified AtSTP11 transporter plays a role in the supply of monosaccharides to growing pollen tubes.